Keketuaan ASEAN dan Potensi Diplomasi Indonesia dalam Penyelesaian Konflik di Myanmar - Ain, Wan Nur; Wulandari, Sephia Dwi Meilinda (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2023)
As the highest decision holder of ASEAN for the next year, Indonesia must be able to address challenges in the region, including the Myanmar conflict that still heating up. The five consensus agreed by ASEAN in 2021 as a peaceful effort in Myanmar, still seem weak to sustain peace. Similar conditions were also experienced by Indonesia in 1976-2005, namely the conflict between the Free Aceh Movement (GAM) and Indonesia which was successfully reconciled through the Helsinki MoU agreement initiated by Vice President Jusuf Kalla and mediated by Finnish President Martti Ahtisaari, representatives of the European Union and ASEAN members. This article aims to explain how Indonesia can utilize its diplomatic potential in facilitating peace for Myanmar in the era of its chairmanship of ASEAN, by reflecting on Indonesia's success in the conflict between GAM and Indonesia. This article uses the literature research method by using journal articles, reports, government legislation and international organizations that have been published through their official websites. The findings presented by the author are that Indonesia should be able to take advantage of its position as chair of ASEAN by optimizing diplomacy through the widest possible dialogue in resolving the Myanmar conflict, as happened in Aceh. Keywords: ASEAN; Indonesia; Myanmar; Consensus; Diplomacy